The Efficacy of Think Talk Write Strategy in Improving Writing Skill for Teenagers at Batu Walenrang Palopo - Masruddin Masruddin; Dewi Furwana; Abdul Jafar (FOSTER: Journal of English Language Teaching, 2021)
This research about the efficacy of think talk write strategy in improving writing skill for teenagers at Batu Walenrang Palopo. The purpose of this research is to find out whether or not the use of think talk write strategy is effective in improving writing skill for teenagers (16th-17th) at Batu Walenrang Palopo. This research applied the pre-experimental method, the research is carried out in one class, the population of this research is teenagers at Batu Walenrang Palopo. The sample of this research are nine teenagers (16th-17th) at Batu Walenrang Palopo. The sampling technique in this research is the total sampling technique. The instrument of this research is writing test. The researcher gives pretest and post-test to the teenagers. the data are analyzed using Spss 20. The result of this research shows that the use of think talk write strategy is effective in writing. It could be proved from the result of the calculation that students score in the post-test is higher than students score in the pre-test. The mean score in Post-test is higher than the mean score of the pre-test P=0.003>0.005. It means that is the use of think talk write strategy is effective in improving writing skill for teenagers (16th-17th) at Batu Walenrang Palopo. The implementation of this research as an alternative for educators in developing students' understanding in learning.